KEBIJAKAN DAN IMPLEMENTASI PROGRAM TAHFIZ AL-QURAN DI SD NEGERI 11 KOTA PADANG - Rendy Nugraha Frasandy; Siti Faizatun Nimah (Murabby: Jurnal Pendidikan Islam, 2019)
The purpose of this study is to find out 1) the policies of the Al-Qur'an tahfiz program in the 11th Elementary School of Padang City, 2) the implementation of the Al-Qur'an tahfiz program in the 11th Elementary School of Padang City. This research uses a descriptive qualitative approach, with observation, interview and documentation research instruments. The results showed that the policy of the Tahfiz program in SD Negeri 11 Padang, was derived from the policies of the Padang city government, through Mayor Regulation No. 33 of 2013 concerning the Tahfiz Al-Qur'an Program in the City of Padang. Al-Qur'an's tahfiz program at the 11th Elementary School of Padang City was implemented in 2015, when the school principal was Ms. Deswati S.Pd. Until now the Al-Qur'an tahfiz program continues to run and get positive interest from the surrounding community. This program is carried out 1x for 1 week using Saturday for 2-3 hours of study each day. This program is classified as extracurricular activities and has been followed by students from grades 3 to 6 elementary school. Especially for grade 6 students, get attention and priority with a target of 1 juz when graduating from elementary school.